EVALUATION OF GENOTOXIC EFFECTS OF ALCOHOLIC EXTRACT OF KALANCHOE PINNATA USING SINGLE CELL GEL ELECTROPHORESIS - V, Saravanan; Ss, Murugan; Jsi, Rajkumar; Krishnan Kr, Navaneetha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to evaluate the genotoxic and mutagenic potentials of Kalanchoe pinnata alcoholic leaves extract. Methods: Single cell gel electrophoresis (COMET assay) was adopted to investigate genotoxicity potential of standardized ethanolic leaves extract at the concentration of 10, 50, and 100 μg/ml, respectively, using human lymphocytes. Results: K. pinnata leaves extract did not completely damage DNA in human lymphocytes but low, medium, and high-level damage was found in with positive control. The DNA damage level decreases in low, medium, and high (12±1, 6±1, and 1±1) without positive control at the concentration of 100 μg/ml. Conclusion: It was concluded that the parent material did not induce mutagenic and genotoxic potentials at the concentrations 10, 50, and 100 μg/ml but its metabolites are inducing genotoxicity in various models.